PEMBERIAN BIOPLUS DAN PAKAN TAMBAHAN DEDAK TERHADAP PERFORMA BOBOT BADAN SAPI PO DI KABUPATEN SUKABUMI (Jurnal Agroekoteknologi dan Agribisnis, 2019)
ABSTRACTBioplus is a probiotic derived from rumen contents containing selectively selected roughage fiber grains and interacts positively with targeted cattle rumen microbes. Provision of bioplus and the addition of rice bran to Ongole Cossbred Cattle in Sukabumi Regency aimeds to increase the daily weight gain (PBBH) of PO cattle. In this study, 16 male bulls aged 2-2.5 years old with body weights of 310kg Â± 16.2 kg were used. The cattle were divided into 4 treatment groups (P0, P1, P2 and P3) each of 4 replications according to a completely randomized design. Catlle in the control group (P0) wasfed with 30 kg of grass + 3 kg of cassava, P1 : P0 + 2.5 kg rice bran, P2: P0 + 2.5kg rice bran + 200 g bioplus and P3 : P0 + 2.5 kg rice bran + 400 g bioplus.The results, showed that the bioplus and rice bran addition significantly increased body weight of PO cattle (P